Literacy and Politics. Angicos, after 50 years - Moacir Gadotti (FahrenHouse, 2014)
This paper doesn't attempt to situate the figure of Paulo Freire in the context of Latin America or international pedagogy. In this paper, the author presents a synthesis of the Angicos (Braisl) political literacy experience, asking what Freire learned from the Angiços experience. The following questions are developed in the paper: How Freire consolidated his pedagogical model through a social science based on a critical hermeneutics? How his thinking evolved into a theory of social and cultural reproduction, looking particularly to the role o education? And, how then Freire moved into a critical social psychology focusing on domination and the developmental pedagogical subject? Freire was inspired by the profound political and pedagogical experience of Angicos and his political pedagogical practice, understood praxis as collective learning. At the conclusion, the author discusses the two obsessions of Freire, already present in the Angicos experience and that stay with him throughout his life: the relationship between democracy, citizenship and education, and education as a postcolonial ethical act of social transformation.  Received: 30/04/2013 / Accepted: 18/09/2013 How to reference this article Gadotti, M. (2014). Alfabetizar e Politizar. Angicos, 50 anos depois. Foro de Educación, 12(16), pp. 51-70. doi: http://dx.doi.org/10.14516/fde.2014.012.016.002